Design and development of novel thiazole-sulfonamide derivatives as a protective agent against diabetic cataract in Wistar rats via inhibition of aldose reductase - Yin Liang (De Gruyter, 2021)
In recent years, ALR2 (aldose reductase) inhibitors have attracted attention for their effective ability to reduce the progression of diabetes-associated cataracts. Therefore, in the present article, we intended to develop novel thiazole-sulfonamide hybrids as a potent inhibitor of ALR2. These molecules significantly inhibited the ALR2 level in the rat lenses homogenate, where the most potent compound 7b showed activity comparable to sorbinil as standard. In Wistar rats, compound 7b improved the insulin level and body weight of the experimental animal together with a reduction in the glucose output. Compound 7b showed a significant reduction in the expression of ALR2 in rat lenses in western blot analysis.